2018
DOI: 10.1098/rsos.181227
|View full text |Cite
|
Sign up to set email alerts
|

A global cline in a colour polymorphism suggests a limited contribution of gene flow towards the recovery of a heavily exploited marine mammal

Abstract: Evaluating how populations are connected by migration is important for understanding species resilience because gene flow can facilitate recovery from demographic declines. We therefore investigated the extent to which migration may have contributed to the global recovery of the Antarctic fur seal (Arctocephalus gazella), a circumpolar distributed marine mammal that was brought to the brink of extinction by the sealing industry in the eighteenth and nineteenth centuries. It is widely believed that animals emig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…It is conceivable that some juveniles, subadults and non-breeders could have escaped the sealers by not coming ashore. However, if this were the case, relict populations should have survived at all of the breeding grounds, whereas our data, together with recent studies and historical accounts, suggest that that Antarctic fur seals may have been locally extirpated at Macquarie, Heard, Crozet and Marion Islands 47,50,51 . We therefore speculate that tiny remnants of once much larger breeding populations may have persisted in a handful of particularly inaccessible locations that were rarely if ever visited by sealers.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…It is conceivable that some juveniles, subadults and non-breeders could have escaped the sealers by not coming ashore. However, if this were the case, relict populations should have survived at all of the breeding grounds, whereas our data, together with recent studies and historical accounts, suggest that that Antarctic fur seals may have been locally extirpated at Macquarie, Heard, Crozet and Marion Islands 47,50,51 . We therefore speculate that tiny remnants of once much larger breeding populations may have persisted in a handful of particularly inaccessible locations that were rarely if ever visited by sealers.…”
Section: Discussionmentioning
confidence: 42%
“…As breeding www.nature.com/scientificreports www.nature.com/scientificreports/ populations were not observed at the other sub-Antarctic islands until the 1950s to the 1980s [39][40][41][42][43][44] , several authors have speculated that the former geographic distribution of this species was likely recolonized from South Georgia 28,38,[45][46][47] . However, a number of studies have reported genetic differences among some of these populations [48][49][50][51] , pointing towards a more complex picture in which more than one relict population may have survived sealing.…”
mentioning
confidence: 99%
“…Also, the records of leucistic individuals over the period under investigation enabled us to find the tendency for the increase in the number of leucistic animals in the successive years although the total population remained unchanged. First incidence of a leucistic individual was noted in 1933 for the population of South Georgia (Bonner 1968) and leucistic animals are relatively prevalent there (Hofmeyr et al 2005), which might be a result of a strong historical bottleneck (Hoffman et al 2011(Hoffman et al , 2018. Leucistic animals were also observed in the South Shetlands, Bouvetøya and Marion Island (Hofmeyr et al 2005;Wege et al 2015), Îles Kerguelen, Macquarie Island, Îles Crozet and Heard Island (Hoffman et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…First incidence of a leucistic individual was noted in 1933 for the population of South Georgia (Bonner 1968) and leucistic animals are relatively prevalent there (Hofmeyr et al 2005), which might be a result of a strong historical bottleneck (Hoffman et al 2011(Hoffman et al , 2018. Leucistic animals were also observed in the South Shetlands, Bouvetøya and Marion Island (Hofmeyr et al 2005;Wege et al 2015), Îles Kerguelen, Macquarie Island, Îles Crozet and Heard Island (Hoffman et al 2018). Analysis of the polymorphism in the melanocortin 1 receptor gene, responsible for cream-coloured phenotype in fur seals, indicates a global cline in the frequency of colour polymorphism and suggests a limited contribution of gene flow between South Georgia and other populations (Hoffman et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation